The Interaction of RecA With Both CheA and CheW Is Required for Chemotaxis - Frutos-Grilo, Elisabet; Marsal, Maria; Irazoki, Oihane; Barbé, Jordi; Campoy, Susana (Frontiers in Microbiology, 2020)
Salmonella enterica is the most frequently reported cause of foodborne illness. As in other microorganisms, chemotaxis affords key physiological benefits, including enhanced access to growth substrates, but also plays an important role in infection and disease. Chemoreceptor signaling core complexes, consisting of CheA, CheW and methyl-accepting chemotaxis proteins, modulate the switching of bacterial flagella rotation that drives cell motility. These complexes, through the formation of heterohexameric rings composed of CheA and CheW, form large clusters at the cell poles. RecA plays a key role in polar cluster formation, impairing the assembly when the SOS response is activated. In this study, we determined that RecA protein interacts with both CheW and CheA. The binding of these proteins to RecA is needed for wild-type polar cluster formation. In silico models showed that one RecA molecule, attached to one signaling unit, fits within a CheA-CheW ring without interfering with the complex formation or array assembly. Activation of the SOS response is followed by an increase in RecA, which rises up the number of signaling complexes associated with this protein. This suggests the presence of allosteric inhibition in the CheA-CheW interaction and thus of heterohexameric ring formation, impairing the array assembly. STED imaging demonstrated that all core unit components (CheA, CheW and MCPs) have the same subcellular location as RecA. Activation of the SOS response promotes the RecA distribution along the cell instead of being at the cell poles. CheA- and CheW- RecA interactions are also crucial for chemotaxis, which is maintained when the SOS response is induced and the signaling units are dispersed. Our results provide new, molecular-level insights into the function of RecA in chemoreceptor clustering and chemotaxis determining that the impaired chemoreceptor clustering not only inhibits swarming but also modulates chemotaxis in SOS-induced cells, thereby modifying bacterial motility in the presence of DNA-damaging compounds, such as antibiotics.